Nematicidal Coumarins from Cnidium monnieri Fruits and Angelica dahurica Roots and Their Physiological Effect on Pine Wood Nematode (Bursaphelenchus xylophilus) - Jiale Feng; Chenglei Qin; Xiaohong Liu; Ronggui Li; Chao Wang; Chunhan Li; Guicai Du; Qunqun Guo (Molecules, 2023)
Pine wood nematode (PWN), Bursaphelenchus xylophilus, is a major pathogen of pine wilt disease (PWD), which is a devastating disease affecting pine trees. Eco-friendly plant-derived nematicides against PWN have been considered as promising alternatives to control PWD. In this study, the ethyl acetate extracts of Cnidium monnieri fruits and Angelica dahurica roots were confirmed to have significant nematicidal activity against PWN. Through bioassay-guided fractionations, eight nematicidal coumarins against PWN were separately isolated from the ethyl acetate extracts of C. monnieri fruits and A. dahurica roots, and they were identified to be osthol (Compound 1), xanthotoxin (Compound 2), cindimine (Compound 3), isopimpinellin (Compound 4), marmesin (Compound 5), isoimperatorin (Compound 6), imperatorin (Compound 7), and bergapten (Compound 8) by mass and nuclear magnetic resonance (NMR) spectral data analysis. Coumarins 1–8 were all determined to have inhibitory effects on the egg hatching, feeding ability, and reproduction of PWN. Moreover, all eight nematicidal coumarins could inhibit the acetylcholinesterase (AChE) and Ca2+ ATPase of PWN. Cindimine 3 from C. monnieri fruits showed the strongest nematicidal activity against PWN, with an LC50 value of 64 μM at 72 h, and the highest inhibitory effect on PWN vitality. In addition, bioassays on PWN pathogenicity demonstrated that the eight nematicidal coumarins could effectively relieve the wilt symptoms of black pine seedlings infected by PWN. The research identified several potent botanical nematicidal coumarins for use against PWN, which could contribute to the development of greener nematicides for PWD control.